Impact Of Corporate Governance Factors On Corporate Social Responsibilities Disclosure: Evidence From Sri Lanka Listed Companies - Muraleetharan, P. (Jaffna Science Association, 2025)
Corporate social responsibility (CSR) refers to the procedures and policies that provide financial and non-financial information regarding effects and harm relating to the environment, employees, society, and consumers in order to improve a company's reputation internationally. This study aims to Impact of Corporate Governance factors on Corporate Social Responsibilities Disclosure: Evidence from Sri Lanka Listed Companies. The primary objective of this study is to examine the Corporate Governance factors that determine corporate social responsibility disclosure in listed companies in Sri Lanka. The determine factors are CEO duality, board size, gender diversity, board independent. The CSR disclosure variables are economic, social and environmental using content analysis method. Researcher looked at data from 80 companies in different industries between 2019 and 2023. The findings reveal several key determinants of CSR disclosure in the Sri Lankan context. Firstly, board size and board independent are positively associated with the level of CSR disclosure, indicating that larger companies tend to disclose more information about their CSR activities. Secondly, board independent has a significant positive effect on CSR disclosure, suggesting that financially stable companies are more likely to engage in CSR reporting.
Keywords: Corporate governance; CSR; Economic; Environmental; Social disclosure